The Influence of the Dow Jones Industrial Average, Standard & Poor’s 500, and Inflation on the Composite Stock Price Index: A VECM Analysis - Lazuardi, Deris; Adlan, Muhamad Aqim (Jurnal Ekonomi Akuntansi dan Manajemen, 2025)
One of the main indicators of the Indonesian economy is the movement of the Composite Stock Price Index (CSPI), which reflects the performance and health of the capital market as a whole. The CSPI itself is also influenced by various factors, both external and internal factors. Researchers aim to analyze the influence of the Dow Jones Industrial Average (DJIA), Standard & Poor’s 500 (S&P 500), and Inflation variables on the Composite Stock Price Index using the Vector Error Correction Model (VECM) model, and data collected from the Month in 2009 to the Month in 2024. Researchers in this study used quantitative methods and the sources used were secondary data sources. Variable sources are taken from Yahoo Finance, Investing.com, and Bank Indonesia data. Researchers used EViews version 13 Enterprise software to analyze the time series data. DJIA has a positive and significant influence on CSPI in the long term. While the DJIA in the short term has a positive and insignificant influence on the CSPI. Regarding the S&P 500 in the long term, the S&P 500 has a negative and insignificant effect on the CSPI. While the S&P 500 in the short term has a negative and significant influence on the CSPI. Then related to Inflation in the long term and short term, Inflation has a positive and insignificant effect on the CSPI. The R2 value is 54%, this indicates a moderate or fairly good influence. Keywords: CSPI, Influence, Dow Jones Industrial Average, Standard & Poor’s 500, Inflation, VECM.